2008
DOI: 10.1164/rccm.200702-296oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Administration of Corticosteroids during Mechanical Ventilation on Rat Diaphragm

Abstract: Rationale: Mechanical ventilation is known to induce ventilatorinduced diaphragm dysfunction. Patients submitted to mechanical ventilation often receive massive doses of corticosteroids that may cause further deterioration of diaphragm function. Objectives: To examine whether the combination of 24 hours of controlled mechanical ventilation with corticosteroid administration would exacerbate ventilator-induced diaphragm dysfunction. Methods: Rats were randomly assigned to a group submitted to 24 hours of contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
4
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 52 publications
4
48
4
7
Order By: Relevance
“…Interestingly, in this study the calpain-inhibiting effect of corticosteroids was shown to depend on the dose administered, being minimal at low concentrations. Recently our group showed that administration of a single high dose of methylprednisolone (80 mg/kg, corresponding ~13 mg/kg in humans) during controlled mechanical ventilation protected the diaphragm from the deleterious effects of prolonged mechanical ventilation through inhibition of the calpain system [9]. This study and a previous CMV study, in which we used a calpain inhibitor [9], confirm the important role of the calpain system in the development of VIDD.…”
Section: Introductionsupporting
confidence: 71%
“…Interestingly, in this study the calpain-inhibiting effect of corticosteroids was shown to depend on the dose administered, being minimal at low concentrations. Recently our group showed that administration of a single high dose of methylprednisolone (80 mg/kg, corresponding ~13 mg/kg in humans) during controlled mechanical ventilation protected the diaphragm from the deleterious effects of prolonged mechanical ventilation through inhibition of the calpain system [9]. This study and a previous CMV study, in which we used a calpain inhibitor [9], confirm the important role of the calpain system in the development of VIDD.…”
Section: Introductionsupporting
confidence: 71%
“…Patients suffering from acute respiratory failure are often treated with corticosteroids for the underlying lung disease or other inflammatory conditions (62). This is significant because glucocorticoid treatment can promote steroid-induced myopathy of both respiratory and limb muscles (60,96).…”
Section: Impact Of Age and Drugs On Mv-induced Diaphragmatic Contractmentioning
confidence: 99%
“…This is significant because glucocorticoid treatment can promote steroid-induced myopathy of both respiratory and limb muscles (60,96). Recent reports have investigated the combined effects of high-dose corticosteroid treatment on diaphragm function in animals using both partial and full support MV (61,62). Unfortunately, these studies have yielded divergent results.…”
Section: Impact Of Age and Drugs On Mv-induced Diaphragmatic Contractmentioning
confidence: 99%
“…During prolonged MV, MV-induced diaphragmatic atrophy develops as a result of an increase in oxidative stress in the muscle fibers (1,31,47), which leads to a decrease in protein synthesis (36) and an increase in protein degradation during which all proteolytic pathways are activated (26,37,47). This is also the case in locomotor skeletal muscles after unloading (3,9), and, furthermore, it is well known that early recovery of these muscles is associated with enhanced oxidative stress (35), proteolysis, and protein synthesis (37) compared with the unloaded muscle.…”
Section: Reloading the Diaphragm Has No Effect On Proteolysismentioning
confidence: 99%
“…The latter because, in ventilator-induced diaphragm dysfunction, the Ca 2ϩ -dependent calpain system and the caspase-3 system have been shown to be one of the most important proteolytic systems, as they are necessary for the initial degradation of actomyosin complexes. In addition, their inhibition has been shown to result in a prevention of the deleterious effects of CMV on the diaphragm (1,26,27). However, no changes could be detected in these markers of protein degradation.…”
Section: Reloading the Diaphragm Has No Effect On Proteolysismentioning
confidence: 99%